Latino mass mobilization: immigration, racialization, and activism - Zepeda-Millán, Chris (Cambridge University Press, 2017)
"In the spring of 2006, millions of Latinos across the country participated in the largest civil rights demonstrations in American history. In this timely and highly anticipated book, Chris Zepeda-Millán analyzes the background, course, and impacts of this unprecedented wave of protests, highlighting their unique local, national, and demographic dynamics. He finds that because of the particular ways the issue of immigrant illegality was racialized, federally proposed anti-immigrant legislation (H.R. 4437) helped transform Latinos' sense of latent group membership into the racial group consciousness that incited their engagement in large-scale collective action. Zepeda-Millán shows how nativist policy threats against disenfranchised undocumented immigrants can provoke a political backlash - on the streets and at the ballot box - from not only 'people without papers', but also naturalized and US-born citizens. Latino Mass Mobilization is an important intervention into contemporary debates regarding immigration policy, social movements, and racial politics in the United States."--Publisher's Web site